Transcending Bodily Boundaries: The Existence of Women in Naguib Mahfouz’s Short Story Tahwida from the Collection Hams al-Nujum through Simone de Beauvoir’s Existential Feminism Perspective - Moch. Julian Rizqy Audi; Abdul Rohman (Information Technology and Science(ITScience), 2025)
This study examines the representation of women's existence through the character of Tawhida in Naguib Mahfouz's short story Tahwida using Simone de Beauvoir's existential feminism perspective. This perspective views women not as objects of patriarchal culture, but as subjects who have awareness, freedom, and authenticity in determining their existence. Using a descriptive qualitative method and a literature review approach, this study focuses on collecting data and information from various written sources, such as books, scientific journals, articles, and documents relevant to this research. This study explores how the body, subjectivity, spirituality, and social relations of the character Tawhida represent women's struggles in facing social constructs that limit their freedom of movement. The results of the study show that Tawhida is not merely a symbol of beauty or domestication, but rather an autonomous, spiritual, and intellectual woman. She transcends the social boundaries that constrain her and demonstrates the ability to consciously interpret her life. In the context of modern Arabic literature, the representation of Tawhida marks a paradigm shift from passive women to active, critical, and empowered subjects. Thus, this study confirms that female characters in literary works can be a means of articulating women's authentic existence, as well as a form of resistance against the objectification and subordination attached to women's bodies and social roles.